O projeto jornal da escola - Tércia Rodrigues Timo (2015)
After realizing that, at the end of High School, students are not able to produce texts as they appear in the practices of reference, the school where we work decided to join the Jornal da Escola Project (School Paper), in an attempt to stimulate the process of textual production. The result of those publications, however, was unsatisfactory. The criticism led us to the base question for this research: How do we transform the paper into an instrument that participates in the formation of critical authors in the school environment? The main aim of this research is to investigate the extent to which the production of a school paper can collaborate for the formation of critical authors. Considering such an aim, the methodology for this work was picked according to a textual-interactional approach, because we understand that the interactional dimension involves and characterizes the textual and discursive production of school paper authors. Our theoretical background is based on Antunes (2010); Bakhtin, (2011 [1953]); Bonini (2011); Bronckart (2012 [1999]); Freinet (1926); Koch e Elias (2011); Lozza (2009); Marcuschi (2001, 2002, 2003, 2008); Melo (2003); Dolz, Noverraz and Schneuwly, (2004); Pécora (1980); Perelman and Olbrechts-Tyteca (2005), among other authors. The corpus for this research is composed of the three first issues of the school paper from an institution focused on basic education, Folha Conexão Santa Clara, as listed: issue 1, from July 2011; issue 2 from November 2011, and issue 3, from November 2012. The results achieved from the project involved its provision for students and teachers of an intense experience of education, teaching and learning; it presupposes the acceptance of criticism and relies on an involvement by the school community and other communities that may be part of the students life. The results on the school paper indicate that: i. in order to capture the reader they present a diversity of sections, genres, themes, approaches; texts must not be monosemantic and repetitive, rendering necessary the presence of multimodal texts, images, resulting in playfulness, quickness in social interaction, at the same time it introduces space for a denser information that implies linguistic competence and persuasion skills in the authors argument; ii. Investing in the publication of opinion pieces is fundamental for the inclusion of the reader in the arena of discussion; iii. Texts representing actual language activities seek the readers focus, its formation of loyalty and propose other actual language activities; iv. The process of separation of the material for text production (interviews, polls, research, photos) demands communicative competence and satisfactory solutions for multiple situations, for internal interaction practices in the process of production of journalistic pieces, product of an intense procedure of intertextuality, dialogism and, in the case of the opinion piece, otherness; v. Bronckarts (2012 [1999] p. 122-129) view of the text as textual layers, or, according to the constitutive elements of the global dimension, axis of coherence, Antunes (2010, p. 55-58) and the didactics of genre in its most peculiar aspects, its usage and social functions; Dolz, Noverraz e Schneuwly (2004) endorse the view that the reader establishes coherence and gets hooked by the meaning effects produced; vi. The actual language activity permits students to exercise argumentation, but, occasionally, exceeds this first training stage and provides real situations for development of critical thinking. Results according to the formation of the critical authors indicate an author-reader of newspaper, a citizen responsible for its social participation, for practicing the right to a particular opinion and understands the strategies of production for a journalistic texts, which does not only broadcast but also manages collective memory, with a permanently responsive attitude (BAKHTIN, 2011 [1953]), questioning in the face of the reader, since the text, in its materiality and as a product of historical discourse, a reaction to ensue other reactions. This research enabled a reflection of the social relevance of this study for teaching Portuguese: The Jornal da Escola project allows students to understand the mechanisms for the production of well-written texts, as directed by the practices of reference, but it also allows a reformulation of the teachers pedagogical practice.